A three-dimensional finite element model of cAMP signals - R. Warren (Elsevier, 2021)
This paper presents a three-dimensional finite element model for cyclic adenosine monophosphate (cAMP) signaling. Governing equations for the synthesis, diffusion, and degradation of cAMP were numerically implemented using the finite element method. Simulated results were displayed as time course plots of cAMP concentrations at selected nodes within the discretized geometry. The validity of the finite element model was assessed by comparing simulated results against analytical or other numerical solutions of cAMP concentration distribution for a spherical cellular volume. An endothelial cell was also simulated using its discretized geometry obtained from microscopic cellular cross-sectional images. Simulated solutions using the spherical cellular volume produced near identical cAMP concentration plots to the analytical solutions and were in good agreements with numerical results obtained from VCell, an existing software package for modeling cell biological systems. The validated 3-D finite element model was then employed to simulate the cAMP signaling pathway within a pulmonary microvascular endothelial cell geometry.